Forced degradation studies of clobetasol 17‐propionate in methanol, propylene glycol, as bulk drug and cream formulations by RP‐HPLC. Issue 5 (28th January 2013) - Fauzee, Ayeshah Fateemah Beebee; Walker, Roderick Bryan
<x xml:space="preserve">Abstract</x> A rapid, simple, stability‐indicating forced degradation study of clobetasol 17‐propionate was conducted using RP‐HPLC. The method was used to analyze clobetasol 17‐propionate in methanol, propylene glycol, and a cream formulation. Isocratic elution of clobetasol and its degradation products was achieved using a Nova‐Pak® 4 μm C18 150 mm × 3.9 mm id cartridge column and a mobile phase of methanol: water (68:32 v/v) at a flow rate of 0.9 mL min−1. Quantitation was achieved with UV detection at 239 nm. Nondegraded clobetasol was eluted at a retention time of 6.0 min. Clobetasol 17‐propionate was subjected to different stress conditions viz., acidic, basic, heat, oxidation, light, and neutral hydrolysis. The greatest degradation occurred under strong base and oxidative conditions. Strong base‐degraded clobetasol produced additional peaks at retention times of 1.8, 4.0, 5.0, and 8.0 min and clobetasol oxidation degradation peaks eluted at 2.2 and 24 min. Complete validation was performed for linearity, accuracy, and precision over the concentration range 0.15–15 μg mL−1. All data were analyzed statistically and this RP‐HPLC method proved to be accurate, precise, linear, and stability indicating for the quantitation of clobetasol 17‐propionate in methanol, propylene glycol, and cream formulations.